WORKSHOP MEDIA PEMBELAJARAN BERBASIS GAME INTERAKTIF UNTUK EVALUASI PEMBELAJARAN DI SMP PGRI 1 BUDURAN SIDOARJO - Restu Ria Wantika; Prayogo; Annisa Dwi Sulistyaningtyas; Erlin Ladyawati; Susilohadi (JURNAL PADI (Pengabdian mAsyarakat Dosen Indonesia), 2022)
Creative and innovative learning media is one of the factors that affect the quality of education that needs to be developed along with the development of digital technology. In this regard, it is necessary to have learning media that can attract students' interest in learning so that the learning atmosphere is more comfortable and fun. In addition, the use of learning media in the teaching and learning process at the same time shows the teacher has made plans in carrying out teaching in the classroom. So that this service activity can provide an overview or additional information related to game-based learning media. The implementation of the service is carried out through three stages, namely: (1) the planning stage; (2) training stage; (3) evaluation of program sustainability. Based on the Community Service Activities carried out, it has succeeded in opening the insight of the teachers of SMP PGRI 1 Buduran Sidoarjo, especially regarding multimedia-based learning media in the form of interactive games. Based on the results of the program evaluation, the majority of teachers were very happy with the training activities carried out. These activities provide an overview and new knowledge related to learning media.